Histological and immune response in the fish Centropomus viridis elicited by the parasite Rhabdosynochus viridisi - Dania López-Moreno; Zeinab Yazdi; Francisco N. Morales-Serna; Juan M. Martínez-Brown; Leonardo Ibarra-Castro; Alejandra García-Gasca; Selene M. Abad-Rosales; Rodolfo Lozano-Olvera; Emma J. Fajer-Ávila; Esteban Soto (Revista MVZ Cordoba)
Objective. To analyze histological and immunological changes in the Pacific white snook (PWS) Centropomus viridis during primary infection and re-infection with the monogenean Rhabdosynochus viridisi. Materials and methods. Samplings were performed at three timepoints (0,1, and 2). Histological alterations in gills were evaluated by the severity degree and the degree of tissue change. RT-qPCR assays were developed to investigate the expression of il1B, il8, il10, il12, il17, igM, igT, ifnγ, tnfα, tbet, hsp70, foxp3a, stat4, and cmip in gills and head kidney. Results. The prevalence of infection was 100% in challenged fish. During the primary infection, the mean intensity was 152 parasites per fish at Time 1 and 94 at Time 2, while in the reinfection, it was 367 parasites at Time 1 and 129 at Time 2. Histological analysis of gills showed fusion of the secondary lamellae, hyperplasia, infiltration of mononuclear inflammatory cells, and increase of chloride cells in both primary infections and reinfections. Only the expression of cmip in gills at Time 1 was significantly higher in reinfections than in primary infections, and the expression of il12β showed a fold-change value >100 in head kidney at Time 2 in primary infections. Conclusions. The monogenean R. viridisi may cause histological alteration in its fish host. As showed by the decrease of the intensity of infection from Time 1 to Time 2, it seems that the PWS is able to combat R. viridisi; however, our immunological analysis did not reveal strong evidence of a possible mechanism.